Manajemen Emosi dan Mindfulness sebagai Strategi Peningkatan Ketahanan Psikologis Pelaku UMKM - R. Amalina Dewi Kumalasari; Astri Firdasannah; Anita Silvianita; Nurafni Rubiyanti; Rahmi Habibah (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2026)
MSME actors face business pressures, customer demands, limited resources, and dual-role responsibilities that can trigger stress and reduce the quality of decision-making. This community service program aimed to strengthen participants’ understanding and basic skills in emotional management and mindfulness as capacities that support psychological resilience. The program involved members of the Rumah Hasanah Bandung Community and employed an experiential learning approach through interactive lectures, discussions, guided practice, reflection, and role play. The training covered emotional concepts, emotion regulation techniques, mindfulness, wise mind, and what skills and how skills. Program effectiveness was evaluated using identical pre-test and post-test questionnaires, supported by structured observations and participant reflections. The results showed that the mean score increased from 2.80 to 4.32, representing a 54.3% improvement, with the greatest gains observed in participants’ understanding of how skills, what skills, and the distinction between wise mind and emotional mind. These findings indicate that the program successfully enhanced participants’ initial capacity to manage emotional challenges encountered in business activities. Continued mentoring and follow-up evaluation are recommended to encourage the consistent application of these skills and to assess their contribution to strengthening the psychological resilience of MSME actors.